2013
DOI: 10.1111/jsr.12063
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict sleep‐disordered breathing in pregnancy? The clinical utility of symptoms

Abstract: Sleep-disordered breathing (SDB) is reported commonly during pregnancy and is associated with an increased risk of adverse maternal and fetal outcomes, but the majority of these data are based upon self-report measures not validated for pregnancy. This study examined the predictive value of screening questionnaires for SDB administered at two time-points in pregnancy, and attempted to develop an 'optimized predictive model' for detecting SDB in pregnancy. A total of 380 women were recruited from an antenatal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 28 publications
(41 reference statements)
3
54
0
Order By: Relevance
“…After this study was initiated, Facco, et al , demonstrated that the BQ has a sensitivity and specificity of 39% and 68%, respectively, while the ESS has a sensitivity and specificity of 36% and 77%, respectively(9). One recent study found a much higher sensitivity and specificity of the BQ among gravidae, but only performed diagnostic testing on women who either did not score as "high risk" in any of the three categories of the BQ or scored as "high risk" in all three categories(10). Thus the sensitivity and specificity in their study may have limited clinical utility among a population with more intermediate scores, or prone to confounding by virtue of inclusion of obesity on the BQ.…”
Section: Discussionmentioning
confidence: 99%
“…After this study was initiated, Facco, et al , demonstrated that the BQ has a sensitivity and specificity of 39% and 68%, respectively, while the ESS has a sensitivity and specificity of 36% and 77%, respectively(9). One recent study found a much higher sensitivity and specificity of the BQ among gravidae, but only performed diagnostic testing on women who either did not score as "high risk" in any of the three categories of the BQ or scored as "high risk" in all three categories(10). Thus the sensitivity and specificity in their study may have limited clinical utility among a population with more intermediate scores, or prone to confounding by virtue of inclusion of obesity on the BQ.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the tools accurately detected OSA during the third trimester, with sensitivities between 14.6 and 33.3%. Wilson and colleagues [12] also found that the BQ had limited predictive abilities, with a sensitivity and specificity of 0.87 and 0.32, respectively. Based on the above evidence, currently available tools may not be optimal in screening for OSA during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…These questionnaires include the Epworth Sleepiness Scale (ESS), the Berlin Questionnaire (BQ), and STOP-BANG Questionnaire. However, studies have found poor predictive values for the ESS [912], BQ [3, 911], and STOP-BANG [11] in pregnant women. A recent meta-analysis also found that the BQ and ESS performed poorly in predicting OSA during pregnancy, and recommended developing a new tool [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations